MEMBACA MENDALAM, MENULIS TERSTRUKTUR: STRATEGI GURU MENGGUNAKAN PETA PIKIRAN UNTUK MEMBIMBING SISWA MENULIS JURNAL BACA - Badrut Tamam; Jeffry Handhika; Dwi Rosita Sari (CV Edujavare Publishing, 2026)
Reading and writing are two interconnected literacy skills that require a structured approach in elementary school. This study aims to describe the strategies used by teachers in guiding fourth-grade students to write reading journals through the integration of intensive reading techniques and mind mapping methods. This qualitative research uses a case study design to explore teaching practices in real classroom contexts. The research was conducted at SD Negeri Jetis, Dagangan District, Madiun Regency, involving classroom teachers and fourth-grade students. Data were collected through in-depth interviews, participatory observation of reading and writing activities, and analysis of student work and lesson plans. Thematic analysis was conducted through data reduction, data display, and conclusion drawing. The findings show that teachers develop three main strategic stages: (1) guiding intensive reading with focus questions to identify key information, (2) assisting in organizing ideas through structured mind mapping, and (3) facilitating the transformation of visual maps into coherent written journal entries. These strategies demonstrate how mind mapping serves as a cognitive bridge that helps students systematically process reading content and express it in written form. This study concludes that the combination of intensive reading techniques and mind mapping methods provides an effective scaffold for developing students' reading journal writing skills.